Exercise Into Pain in Chronic Rotator Cuff-Related Shoulder Pain: A Randomized Controlled Trial with 6-Month Follow-Up [Response to Letter] - Cavaggion C; Luque-Suarez A; Voogt L; Juul-Kristensen B; Wollants G; Beke L; Fransen E; Struyf F (Open Access Journal of Sports Medicine)
Claudia Cavaggion,1 Alejandro Luque-Suarez,2,3 Lennard Voogt,4,5 Birgit Juul-Kristensen,6 Guy Wollants,7 Lucas Beke,7 Erik Fransen,8 Filip Struyf1 1Research Group MOVANT, Department of Rehabilitation Sciences and Physiotherapy (REVAKI), Faculty of Medicine and Health Sciences, University of Antwerp, Wilrijk, Belgium; 2Faculty of Health Sciences, Universidad de Malaga, Malaga, Spain; 3Instituto de Investigacion Biomedica de Malaga (IBIMA), Malaga, Spain; 4Rotterdam University of Applied Sciences, Department of Physical Therapy Studies and Research Centre for Health Care Innovations, Rotterdam, the Netherlands; 5Pain in Motion Research Group (PAIN), Department of Physiotherapy, Human Physiology and Anatomy, Faculty of Physical Education and Physiotherapy, Vrije Universiteit Brussel, Brussels, Belgium; 6Department of Sports Science and Clinical Biomechanics, University of Southern Denmark, Odense M, Denmark; 7Groepspraktijk Beke & Wollants, Hove, Belgium; 8Center of Medical Genetics, University of Antwerp and Antwerp University Hospital, Edegem, BelgiumCorrespondence: Alejandro Luque-Suarez, Faculty of Health Sciences, Universidad de Malaga, Arquitecto Penalosa s/n, Malaga, 29002, Spain, Email aluques@uma.es